Gingival crevicular fluid and saliva. Issue 1 (February 2016) - Taylor, John J.; Preshaw, Philip M.
Abstract: Understanding the structure and function of the mouth, its tissues and secretions is of great interest to physiologists, cell biologists, immunologists and microbiologists but is also of fundamental interest to the dental professional interested in comprehending the aberrant processes associated with oral disease and in the application of effective clinical interventions. The field of periodontology, which has a truly multidisciplinary perspective cutting across leading edge molecular and cellular biology, clinical dentistry, epidemiology and behavioural science, exemplifies this. A paradigm shift in recent years has led to the consideration of the oral cavity (and, thus, oral disease) not in isolation but as a component integrated with systemic physiology, important in maintaining systemic health and reflective of systemic disease; this has served to promote periodontology, in particular, into the forefront of medicine in general. This volume of Periodontology 2000 considers the role of gingival crevicular fluid and saliva in physiological function, maintenance of oral tissue integrity, defense against pathogens and oral disease as well as the many, emerging applications of analysis of these fluids in support of periodontal disease diagnosis, prognosis and epidemiology. However, whilst the emphasis is on periodontal disease, the wider contexts of oral and systemic health are also key considerations.